1999
DOI: 10.1080/00016489950180207
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Study of Cell Proliferation using BrdU Labelling on Tympanic Membrane, External Auditory Canal and Induced Cholesteatoma in Mongolian Gerbils

Abstract: The Mongolian gerbil is a well-known animal model for induction of aural cholesteatomas. This animal model is useful for studying changes in the keratinizing epithelium. It is not known whether keratin accumulation can increase the proliferative activity of the keratinizing epithelium in tympanic membrane and meatal skin. In this study, we investigated the proliferative activity of the epidermis in induced aural cholesteatoma at various stages and in different areas of the tympanic membrane and meatal skin in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…They indicated that the thickness of the fibrous layer was almost doubled, mostly because of an increased amount of collagen fibers, and the acoustic stiffness was significantly increased in all cholesteatoma ears. Park et al investigated the immunohistochemical study of cell proliferation using BrdU labeling [37] and the expression of PLG-gamma1, ligand-mediated signal transduction for cell proliferation [38] on the tympanic membrane, external auditory canal, and induced cholesteatoma in gerbils. According to the results, the induced aural cholesteatoma showed a more active proliferation center of the epithelial cell and more intense immunolabeling of PLG-gamma1 protein than the eardrum and external ear canal of the normal gerbil.…”
Section: Ligation Of the External Ear Canal Model In The Mongolianmentioning
confidence: 99%
“…They indicated that the thickness of the fibrous layer was almost doubled, mostly because of an increased amount of collagen fibers, and the acoustic stiffness was significantly increased in all cholesteatoma ears. Park et al investigated the immunohistochemical study of cell proliferation using BrdU labeling [37] and the expression of PLG-gamma1, ligand-mediated signal transduction for cell proliferation [38] on the tympanic membrane, external auditory canal, and induced cholesteatoma in gerbils. According to the results, the induced aural cholesteatoma showed a more active proliferation center of the epithelial cell and more intense immunolabeling of PLG-gamma1 protein than the eardrum and external ear canal of the normal gerbil.…”
Section: Ligation Of the External Ear Canal Model In The Mongolianmentioning
confidence: 99%
“…Наиболее часто встречается спонтанная ХНСП, причиной развития которой является снижение с возрастом (средний возраст наблюдаемых пациентов составил 43 года) нормальной миграционной способности эпидермиса наружного слухового прохода [6]. Кроме этого, ее образование связывают с нарушением клеточной пролиферации в условиях избыточного накопления слущенного эпидермиса [7].…”
unclassified